2023
DOI: 10.1055/a-2191-7510
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin for Long-Term Therapy of Venous Thromboembolism in Patients with Cancer and Renal Insufficiency

Patricia Sigüenza,
Juan J. López-Núñez,
Conxita Falgá
et al.

Abstract: Background: The optimal therapy of venous thromboembolism (VTE) in cancer patients with renal insufficiency (RI) is unknown. Current guidelines recommend to use low-molecular-weight heparin over direct oral anticoagulants to treat VTE in cancer patients at high-risk for bleeding. Methods: We used the RIETE registry to compare the 6-month incidence rates of: 1) VTE recurrences vs. major bleeding; and 2) fatal pulmonary embolism (PE) vs. fatal bleeding in 3 subgroups (those with mild, moderate, or severe RI) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
1
0
2
Order By: Relevance
“…In general, these studies have shown that DOACs could be a superior therapeutic option for managing cancer-associated thromboembolism compared to low-molecular-weight heparin. Despite these results, low-molecular-weight heparins, particularly enoxaparin, an anti-factor Xa, are still frequently used in Spain among patients with cancer [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies have shown that DOACs could be a superior therapeutic option for managing cancer-associated thromboembolism compared to low-molecular-weight heparin. Despite these results, low-molecular-weight heparins, particularly enoxaparin, an anti-factor Xa, are still frequently used in Spain among patients with cancer [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…хворих із ТЕЛА майже кожний пʼятий має злоякісне захворювання [6,9], тому в рекомендаціях з ведення хворих із ТЕЛА відзначено обовʼязкове обстеження цих хворих для спростування онкопатології, особливо у випадку відсутності явних причин тромбозу [2][3][4][5][6]. Розвиток ВТЕУ значно погіршує прогноз хворих на онкологічну патологію і часто стає причиною смерті [14][15]19].…”
unclassified
“…У сучасних рекомендаціях [3][4][5][6]15] запропоновано критерії високого ризику смерті хворих із гострою ТЕЛА в госпітальний період, які відображають стабільність гемодинамічних показників. Запропо но вана шкала PESI [5][6][7][8][9], яка дає змогу в гемодинамічно стабільних пацієнтів з «невисоким ризиком» провести стратифікацію вірогідності смерті в госпітальний період. Але залишається недостатньо вивченим питання щодо визначення чинників, повʼязаних із ризиком смерті від ТЕЛА саме онкологічних пацієнтів.…”
unclassified